The three-dimensional course of cranial development of very preterm infants during the first year of life - Santander, P.; Quast, A.; Hubbert, J.; Meyer-Marcotty, P.; Hensel, K.O.; Bergmann, C.; Schmidt, S.; Dieks, J.K. (Early human development, 2024)
Cranial measurements are crucial for evaluating preterm general development because they are a surrogate tool for evaluating brain growth. Usually, they are based on tape-measured head circumference; however, a three-dimensional (3D) approach expands the diagnostic spectrum to the evaluation of cranial volume and shape. Very preterm (vPT) infants face multiple risks and obstacles in their early development. In this study, we analyze the risk for cranial anomalies of vPT compared with term-born (TB) infants during the first year of life. In this single-centre prospective cohort study, 23 vPT and 24 TB healthy infants were assessed. At term equivalent age (TEA) of vPT and time of birth of TB, and 1, 3, 6 and 12 months of postmenstrual age, respectively, a 3D head scan was performed and cephalometrically evaluated regarding cranial growth (head circumference, cranial volume) and shape. Head circumference and cranial volume showed a similar course in vPT and TB. Cranial shape differed significantly between vPT and TB. At TEA, vPT showed longer and narrower heads (dolichocephaly), a difference that disappeared around the 6th month of life. Presence of plagiocephaly was initially similar in vPT and TB, with an increasing difference between both groups with a peak at six months when 34.8 % of the vPT versus none of the TB showed a moderate to severe plagiocephaly (p = 0.004). In vPT, cranial volume significantly correlated with cranial shape, whereas dolichocephaly at TEA had no influence on the further course of plagiocephaly. Cranial development of vPT follows a different course than of TB in terms of cranial shape anomalies, while cranial growth remains unaffected. German Clinical Trials Register number: DRKS00022558. •The preterm cranial growth rate is equivalent to that of full-term born infants during the first year of life•Preterm head shape differs from full-term born infants during the first 6 months of life in terms of head shape anomalies•After the 6th month until the first year of life, the preterm head spontaneously normalizes with an outcome similar to that of full-term born infants in terms of head shape anomalies